Pengaruh Suhu Pengeringan Terhadap Karakteristik Minuman Serbuk instan Sari Kacang Merah (Phaseolus vulgaris L.) - Setiawan, Vanessa; Wisaniyasa, Ni Wayan; Putra, I Gede Arie Mahendra (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 14 No 1 (2025): Jurnal ITEPA, 2025)
Red beans can be processed into instant powdered drinks. The process of making instant powdered drinks is through a drying process, however the drying process at an inappropriate temperature can cause damage to the nutritional components of the food. Therefore, this research was conducted to determine the effect of drying temperature on the characteristics of instant red bean juice powder drinks and to obtain the right drying temperature to produce instant red bean juice powder drinks with the best characteristics. This research used a Completely Randomized Experimental Design with drying temperature treatment consisting of 5 levels, namely 60°C, 65°C, 70°C, 75°C, and 80°C. Each level was repeated three times, so that 15 experimental units were obtained. The parameters observed included yield, solubility, dissolution time, water content, ash content, total sugar, protein content, and sensory acceptance. The data obtained was analyzed using variance and if the treatment had a real effect, it was continued with the Duncan Multiple Range Test (DMRT). The results showed that drying temperature had an effect on yield, solubility, dissolving time, water content, protein content, aroma (scoring) and taste (scoring), but had no effect on ash content, total sugar and sensory characteristics. Drying temperature of 80°C produces the best characteristics of red bean instant powder drink with yield 11.11%, solubility 54.36%, dissolution time 25.49 s, water content 1.12%, ash content 1.78%, total sugar 41.54%, protein content 10.58%, normal color, aroma somewhat like and somewhat typical of red beans, taste normal and somewhat typical of red beans, and overall acceptance is normal.. Keywords: red bean, instant powder drink, drying temperature